Why elite long jumpers do not take off at 45 degrees - Seyfarth, A.; van Leeuwen, J. L.
Long jumpers approach the board at maximum running speed with an angle of attack of about 65 degrees, and take off with an angle of the velocity vector of about 20-25 degrees. Running speed is strongly correlated to the jumping distance (Hay 1993). Although there are a lot of statistical descriptions of the long jump, there is only a limited number of mechanical studies (Hatze 1981, Alexander 1990). With a simple mechanical model based on Alexander (1990), we show that the take-off angle is nearly independent for variations in the angle of attack below 70 degrees.